2018
DOI: 10.3748/wjg.v24.i21.2311
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional steroid is beneficial in benign refractory esophageal strictures: A meta-analysis

Abstract: AIMTo analyze the effect of intralesional steroid injections in addition to endoscopic dilation of benign refractory esophageal strictures.METHODSA comprehensive search was performed in three databases from inception to 10 April 2017 to identify trials, comparing the efficacy of endoscopic dilation to dilation combined with intralesional steroid injections. Following the data extraction, meta-analytical calculations were performed on measures of outcome by the random-effects method of DerSimonian and Laird. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…Различный патогенез и связанный с ним потенциально различный эффект лечения затрудняют интерпретацию результатов, поскольку число пациентов в каждой подгруппе часто невелико [14]. Учитывая выраженный противовоспалительный и противоотечный механизм действия глюкокортикоидов, можно предположить, что инъекции стероидных препаратов смогут уменьшить степень плотности рубцовой ткани и улучшить результаты эндоскопического лечения стриктур, склонных к рецидивированию [15,16].…”
Section: Discussionunclassified
“…Различный патогенез и связанный с ним потенциально различный эффект лечения затрудняют интерпретацию результатов, поскольку число пациентов в каждой подгруппе часто невелико [14]. Учитывая выраженный противовоспалительный и противоотечный механизм действия глюкокортикоидов, можно предположить, что инъекции стероидных препаратов смогут уменьшить степень плотности рубцовой ткани и улучшить результаты эндоскопического лечения стриктур, склонных к рецидивированию [15,16].…”
Section: Discussionunclassified
“…The study showed that adding steroid injection to dilation was effective for anastomotic strictures but not for caustic strictures. A meta-analysis by Szapary et al [25] evaluated intralesional steroid injections for all benign refractory esophageal strictures and showed that steroid injections increased the time between dilations. However, dysphagia scores did not show much improvement after steroid injections.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal dilatation can be performed repeatedly according to schedule and using various dilators such as Maloney-Hurst, Savary-Gilliard, and Balloon dilator under the endoscopy, fluoroscopy, or both. Alternative Acute Management in Corrosive Ingestion DOI: http://dx.doi.org/10.5772/intechopen.101475 methods for post-corrosive esophageal stricture such as esophageal stenting [21,37,38], intralesional steroids [21,[39][40][41][42][43], and, Mitomycin-C [21,[44][45][46][47][48] have been published with various outcomes. These options might supplement dilation with better results.…”
Section: Stricturementioning
confidence: 99%